PENGARUH KREATIVITAS DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PRODI MANAJEMEN FEB UNIRAYA - Nur Indah Lestari Daeli (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The aim of this research is to determine the influence of creativity and entrepreneurship education on entrepreneurship interest in FEB UNIRAYA Management Study Program students. The type of research is quantitative. The data source is all FEB Management study program students who study entrepreneurship courses, from semester 3 students onwards, a sample of 79. The data collection technique is distributing questionnaires to respondents. The data analysis method used is multiple regression analysis. The research results show that partially, Creativity (X1) has a significant effect on Entrepreneurial Interest (Y) of FEB UNIRAYA management students, tcount = 3.982 > ttable = 1.664. Entrepreneurship Education (X2) has a significant effect on Entrepreneurship Interest (Y) of FEB UNIRAYA management students, tcount = 3.689 > ttable = 1.664. The results of the simultaneous test (F test), show that Creativity (X1) and Entrepreneurship Education (X2) have a significant effect on Entrepreneurship Interest (Y) of FEB UNIRAYA management students, Fcount = 16.602 > Ftable = 2.72. The coefficient of determination (R2) is 0.529, expressed as 52.9%. Interest in entrepreneurship is explained by creativity and entrepreneurship education.